2015
DOI: 10.1016/j.immuni.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-CpG Binding Protein 2 Regulates Microglia and Macrophage Gene Expression in Response to Inflammatory Stimuli

Abstract: Summary Mutations in MECP2, encoding the epigenetic regulator methyl-CpG-binding protein 2, are the predominant cause of Rett syndrome, a disease characterized by both neurological symptoms and systemic abnormalities. Microglial dysfunction is thought to contribute to disease pathogenesis, and here we found microglia become activated and subsequently lost with disease progression in Mecp2-null mice. Mecp2 was found to be expressed in peripheral macrophage and monocyte populations, several of which also became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
222
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(256 citation statements)
references
References 48 publications
20
222
5
Order By: Relevance
“…Although careful studthat MeCP2 is required for general neuronal health is underscored by the dysfunction associated with the many different neuronspecific Mecp2 KOs (43,61,(63)(64)(65). In contrast, removal of MeCP2 from astrocytes or microglia results in mild behavioral phenotypes without affecting lifespan (66,67). Thus, the function of MeCP2 in the glial cell types assayed does not appear to drive pathogenesis, though Mecp2 expression in astrocytes improves the breathing symptoms of mice lacking MeCP2 in all other cell types (66).…”
Section: From Patient To Protein: the Molecular Function Of Mecp2mentioning
confidence: 99%
“…Although careful studthat MeCP2 is required for general neuronal health is underscored by the dysfunction associated with the many different neuronspecific Mecp2 KOs (43,61,(63)(64)(65). In contrast, removal of MeCP2 from astrocytes or microglia results in mild behavioral phenotypes without affecting lifespan (66,67). Thus, the function of MeCP2 in the glial cell types assayed does not appear to drive pathogenesis, though Mecp2 expression in astrocytes improves the breathing symptoms of mice lacking MeCP2 in all other cell types (66).…”
Section: From Patient To Protein: the Molecular Function Of Mecp2mentioning
confidence: 99%
“…It was previously shown that MeCP2-overexpressing mice have increased corticosterone release after stress (25), and multiple groups have directly linked MeCP2 to glucocorticoid response (13,23,24), which may explain the increased corticosterone we observed during influenza infection in MeCP2 Tg3 mice. In addition, glucocorticoids can suppress the function of and cause apoptosis in lymphocytes (26), potentially helping to explain the deficiency and impairment of lymphocytes seen late during infection.…”
Section: Discussionmentioning
confidence: 63%
“…Previous reports have implicated MeCP2 in the control of glucocorticoid response (13,23,24). In addition, MeCP2-overexpressing mice have been shown to have an enhanced response to stress (25).…”
Section: And D) This Widespread Neutrophilia Suggested Global Exmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, MBD2 has a role in T-cell development that is partially dependent on the methylation status of critical genes such as Foxp3 [50,66], but also has a role in the innate immune system to indirectly affect T-cell activation and differentiation [49]. Interestingly, both MeCP2 and MBD1 have also been implicated in innate and adaptive immunity [67][68][69] indicating that MBD family proteins may have a wider role in these systems. In the intestine, loss of MBD2 is linked to altered gene expression [61].…”
Section: Discussionmentioning
confidence: 99%